UTILIZATION OF RED MUD TO RECOVER IRON BY COAL REDUCTOR USING ISOTERMAL-GRADIEN TEMPERATURE METHOD - IKHBAL ZAMZAMMI - Nim: 12514024 , AHMAD
Red mud is a solid waste generated by Bayer process in alumina processing. It is generated about 0.8-1.5 ton red mud per ton alumina. The amount of red mud produced by the alumina industry in Indonesia about 480,000-900,000 tons per annum. Red mud cause environmental problem due to its high alkali properties. On the other hand, red mud contains about 14-31% Fe. Therefore, red mud can be used as alternative raw material of steel. In this experiments, red mud from Tayan, West Kalimantan, is done reduction using coal reductor with isothermal-gradient temperature method to obtain iron nuggets. The experiments studied the effect of final temperature, gradien temperature, and effect of CaO and Na2CO3 to the percentage of iron nuggets. The study began with preparation of red mud, coal, CaO, and Na2CO3. Initial characterization was done on red mud with XRD and XRF method. Then red mud is agglomerated into briquette and reduced in furnace with a certain variation. The optimum result of each variation is used fixed variable on the next variation. First, the final temperature variations are done at 1300 0C, 1350 0C, 1400 0C, 1450 0C, and 1500 0C. Secondly, gradien temperature variations perform at 6.67 0C/min, 8.83 0C/min, and 10 0C/min. Finally, variations of additive CaO and Na2CO3 were added by 0%, 2.5%, 5%, 7%, and 10% respectively. The result of the reduction of iron nuggets weighed by weight then analyzed with optical microscope, SEM-EDS Mapping. While slag is analyzed by XRD. The results showed that the highest percentage of iron yield at final temperature variation was obtained at 1500 0C (10 0C/min) that is 66.72%, while in gradien temperature variation was obtained at 10 0C/min (1450 0C) that is 65.36%. The variation of CaO, the highest percentage of iron yield was obtained in the addition of 7.5% CaO (1450 0C, 10 0C/min) that is 70.43%, while the variation of Na2CO3 was obtained at 10% Na2CO3 (1450 0C, 10 0C/min) that is 72.39%. The results of SEM-EDS and X-ray mapping without fluxes, showed that the iron nugget composition consist of 83.97% Fe, 13.4% C, and the rest is Si and S, while in addition the mixture fluxes is 82.20% Fe , 13.89% C, 3.1% S and the rest is Si.